LITERATURE STUDY: MENTAL ACCOUNTING, TRANSPARENCY AND ACCOUNTABILITY IN SDGS 16 - Syahputri , Puja Paradila; Fadillah , Rian; Suherman , Acep (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The purpose of this study is to determine the role of mental accounting, transparency and accountability to SDGs 16 in various aspects and economic sectors. This study uses a literature study method. The results of this study show that mental accounting, transparency, and accountability play an important role in investment decision-making, interim optimization and life cycle of consumer behavior, financial reporting, taxpayer compliance, shareholder decisions, budget performance, management of village fund allocation and public trust in increasing public trust. Although there are some differences in the results of the study related to the influence of mental accounting and transparency on investment decisions and shareholder decisions, mental accounting, transparency and accountability consistently show a positive influence on the quality of investment decision-making, financial reporting, taxpayer compliance, budget performance, village fund allocation management and public trust in increasing public trust. This shows the importance of applying the principles of mental accounting, transparency, and accountability in various contexts to achieve sustainable development goals, especially in achieving SDGs 16. By implementing various strategies, such as education, regulation, increased access to financial information and technology support, the government plays an important role in promoting healthy mental accounting, accountability, and transparency in various aspects of people's lives. In increasing the application of mental accounting positively, every individual must animate all aspects in budget orientation, self-control, value for money benefit orientation. By understanding how mental accounting works and implementing the right strategies, governments, companies and society can make more rational financial decisions, looking at the long-term benefits.